2009
DOI: 10.1177/0002716209334119
|View full text |Cite
|
Sign up to set email alerts
|

Gendered or Gender-Neutral Care Politics for Fathers?

Abstract: This article analyzes how two different policy measures affect gender equality in child care. In the 1990s, Norway introduced two care policies reflecting different ideas about gender and family life. The fathers' quota policy supports the dual-earner family model while the cash-for-care scheme is based on a family model, providing cash benefits irrespective of the parent's work activities. The father's quota is a gendered policy because six weeks of the parental leave period is reserved for the father. Cash-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 7 publications
0
60
0
9
Order By: Relevance
“…Studies have suggested that fathers taking longer parental leaves are later more likely to be involved in childcare (Pleck, 1993;Nepomnyaschy & Waldfogel, 2007). In order to foster greater father involvement in families, some countries have amended parental leave policies so as to reserve some time for fathers only, and fathers are far more likely to take leave under these conditions (Armenia & Gerstel, 2006;Brandth & Kvande, 2009;Haas & Hwang, 2009;Morgan, 2009;Moss & Kamerman, 2009). For example, Swedish fathers receive two non-transferable months of leave (Haas & Hwang, 2009), which has resulted in a dramatically increased father leave-taking rate (Klinth, 2009).…”
Section: Background Parental Leave Policy and Men's Use Of Leavementioning
confidence: 99%
“…Studies have suggested that fathers taking longer parental leaves are later more likely to be involved in childcare (Pleck, 1993;Nepomnyaschy & Waldfogel, 2007). In order to foster greater father involvement in families, some countries have amended parental leave policies so as to reserve some time for fathers only, and fathers are far more likely to take leave under these conditions (Armenia & Gerstel, 2006;Brandth & Kvande, 2009;Haas & Hwang, 2009;Morgan, 2009;Moss & Kamerman, 2009). For example, Swedish fathers receive two non-transferable months of leave (Haas & Hwang, 2009), which has resulted in a dramatically increased father leave-taking rate (Klinth, 2009).…”
Section: Background Parental Leave Policy and Men's Use Of Leavementioning
confidence: 99%
“…Dans une perspective libérale, les individus devraient, après tout, pouvoir décider par eux-mêmes comment diviser leur propre congé parental et, avec un peu de chance, ils choisiraient de le diviser également. Toutefois, comme le démontrent des études sur l'impact des congés parentaux indifférenciés (soit les congés pouvant être partagés librement entre le père et la mère, sans égard pour leur sexe), loin d'encourager une division égale du congé entre les deux parents, ce type de mesure semble, au contraire, renforcer la dichotomie genrée entre le care et le travail rémunéré (Brandth et Kvande, 2009 ;Leira, 2010). Les femmes sont, en effet, beaucoup plus susceptibles que les hommes de prendre l'entièreté du congé parental.…”
Section: Champions Du « Global Gender Gap Ranking »unclassified
“…Accordingly, LPL [Liberal Principle of Legitimacy] imposes a presumption in favor of enacting the gentlest intervention sufficient to accomplish the objective in question. » (Schouten, 2013 : 379) laquelle la mère est la mieux habilitée à s'occuper des enfants et des tâches ménagères, ainsi que les normes rendant la masculinité incompatible avec le care, expliqueraient donc, en partie, ce partage (Brandth et Kvande, 2009). Bien que ces idées tendent à changer avec le temps, force est de constater qu'elles sont, encore aujourd'hui, relativement répandues dans la population 29 .…”
Section: Vers Une Réelle éGalité Des Opportunitésunclassified
“…Other 29 countries provide parental leave, and the length of leave available in those countries (including maternity, parental and childcare leave) ranges from 9 to 15 months, and in some countries it can last for three years or more. For details see Moss (2012, p. 20). on of the policies of the fathers' quota has increased parental leave take-up by fathers in Sweden, Norway, and Iceland (Brandth & Kvande, 2009;Gislason, 2004;Nyman & Pettersson, 2002).…”
Section: Different Types Of Leavementioning
confidence: 99%
“…The main objectives of the policies encouraging fathers to take parental leave are to support gender equality and to strengthen the father-child relationship (Brandth, 2013). The gender division of parental leave can be understood as an indicator of gender equality since sharing parental leave between the mother and the father supports gender equality in childcare, housework and the labour market (Almqvist & Duvander, 2014).…”
Section: Different Types Of Leavementioning
confidence: 99%